Degradation of deoxynivalenol in wheat by double dielectric barrier discharge cold plasma: identification and pathway of degradation products. (21st January 2023) - Zhang, Min; Ye, Zhumiao; Xing, Changrui; Chen, HongJuan; Zhang, Jianhao; Yan, Wenjing
Abstract: Background: Deoxynivalenol (DON) produced during the onset of fusarium head blight not only affects the quality and safety of wheat but also causes serious harm to human and livestock health. However, due to the high stability of DON, it is difficult to eliminate it or reduce it naturally after it has been produced. Cold plasma technology is a non‐thermophysical processing technology that has been widely used for microbial inactivation and mycotoxin degradation. In this study, the degradation efficiency of double dielectric barrier discharge (DDBD) cold plasma on DON in aqueous solution and wheat was studied; the structures of degradation products of DON and its pathway were clarified, and the effect of DDBD plasma on wheat quality was evaluated. Results: Double dielectric barrier discharge cold plasma was used for efficient degradation of DON (0.5 ~ 5 μgmL^‐1) solution and achieved a degradation rate of 98.94% within 25 min under the optimal conditions (voltage 100 V, frequency 200 Hz, duty cycle 80%). Furthermore, 10 degradation products (C15 H24 O5, C15 H22 O6, C15 H22 O9, C16 H22 O7, C15 H20 O7, C15 H20 O9, C15 H18 O8, C15 H22 O5, C16 H24 O5, and C15 H18 O9 ) were identified by ultra‐performance liquid chromatography‐time of flight‐mass spectrometry (UPLC‐TOF‐MS/MS) combined with Metabolitepilot and Peakview software. The degradation pathway of DON was obtained based on the chemical structures and accurate mass of these products. The DON degradation rate of 61% in wheat was achieved after treatment for 15 min, which slightly affects the moisture content, proteins, and wheat starch. Conclusion: Applying DDBD to wheat could effectively reduce the level of DON contamination, which provides a theoretical basis for applying cold plasma to the degradation of DON in wheat. © 2022 Society of Chemical Industry.